2004
DOI: 10.1176/appi.ajp.161.8.1334
|View full text |Cite
|
Sign up to set email alerts
|

Physical Health Monitoring of Patients With Schizophrenia

Abstract: The conference participants recommended that mental health care providers perform physical health monitoring that typically occurs in primary care settings for their patients who do not receive physical health monitoring in those settings. This change in usual practice is recommended on the basis of the conference participants' belief that this additional monitoring will result in the earlier detection of common, serious risk factors that could, without detection and intervention, contribute to impaired health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
529
0
24

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 728 publications
(562 citation statements)
references
References 68 publications
5
529
0
24
Order By: Relevance
“…Risk for CVD and overall mortality due to CVD is elevated in patients suffering from schizophrenia compared to the general population, with mortality rates in this population being at least two times higher than in general population and CVD being responsible for as much as 50% of the excess mortality [16,17]. Recently, there has been an increased awareness of the physical needs of patients with mental illness and several psychiatric clinics, including ours, have set up physical health screening [11,18]. Such screening has unmasked a substantial degree of pathology, especially metabolic disturbances considered as CVD risk factors, including diabetes mellitus [10,11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Risk for CVD and overall mortality due to CVD is elevated in patients suffering from schizophrenia compared to the general population, with mortality rates in this population being at least two times higher than in general population and CVD being responsible for as much as 50% of the excess mortality [16,17]. Recently, there has been an increased awareness of the physical needs of patients with mental illness and several psychiatric clinics, including ours, have set up physical health screening [11,18]. Such screening has unmasked a substantial degree of pathology, especially metabolic disturbances considered as CVD risk factors, including diabetes mellitus [10,11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with schizophrenia have other physical health problems that might be related to the BH response. For example, patients with schizophrenia are at increased risk of cardiovascular disease diabetes, hyerplipidemia, and hypertension (Hennekens et al, 2005;Marder et al, 2004). Perhaps one of these health problems (or their pharmacologic treatment) might explain the increase in the BH response in patients.…”
Section: Discussion Of Breath Hold Resultsmentioning
confidence: 99%
“…Marder et al (9) recommended that the patient's body mass index (BMI) should be recorded before medication initiation or change and at every visit for the first 6 months. The patient should be weighed (and the BMI recorded) at least quarterly when he stabilizes, and more often if he is overweight.…”
Section: Weight Gainmentioning
confidence: 99%
“…Consensus guidelines have been published which elaborate on the differences in risk between agents and provide specific monitoring recommendations (9,19,20). However, a recent study showed that the rate of screening for metabolic side effects of atypical antipsychotics is still low (21).…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation